2008
DOI: 10.1083/jcb.200808137
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of IFT20 in the mouse kidney causes misorientation of the mitotic spindle and cystic kidney disease

Abstract: Primary cilia project from the surface of most vertebrate cells and are thought to be sensory organelles. Defects in primary cilia lead to cystic kidney disease, although the ciliary mechanisms that promote and maintain normal renal function remain incompletely understood. In this work, we generated a floxed allele of the ciliary assembly gene Ift20. Deleting this gene specifically in kidney collecting duct cells prevents cilia formation and promotes rapid postnatal cystic expansion of the kidney. Dividing col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
245
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(264 citation statements)
references
References 32 publications
14
245
2
3
Order By: Relevance
“…Conventional Ift57 and Kif3a/ Kif3b null mutations in mice lead to early embryonic lethality due to left-right axis defects, accompanied by a loss of nodal cilia (14)(15)(16), suggesting that the IFT-B complex is critical for ciliogenesis. Supporting this idea, the deletion of Ift20 in mouse kidney causes a lack of primary cilia and leads to polycystic kidney disease (17). In addition to the traditional role of IFT in cilium assembly, recent studies have found that an IFT-like particle organized by IFT20 is recruited to the immune synapse for T-cell receptor recycling (18,19).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Conventional Ift57 and Kif3a/ Kif3b null mutations in mice lead to early embryonic lethality due to left-right axis defects, accompanied by a loss of nodal cilia (14)(15)(16), suggesting that the IFT-B complex is critical for ciliogenesis. Supporting this idea, the deletion of Ift20 in mouse kidney causes a lack of primary cilia and leads to polycystic kidney disease (17). In addition to the traditional role of IFT in cilium assembly, recent studies have found that an IFT-like particle organized by IFT20 is recruited to the immune synapse for T-cell receptor recycling (18,19).…”
mentioning
confidence: 81%
“…To characterize the function of IFT20 in facial development, we disrupted Ift20 in a neural crest-specific manner using the wingless-related MMTV integration site 1 (Wnt1)-Cre driver line (17,29) (Fig. S1 A and B; Ift20:Wnt1-Cre or cKO hereafter).…”
Section: Disruption Of Ift20 In Neural Crest Cells Results In Craniofmentioning
confidence: 99%
“…In the ciliate Tetrahymena thermophila, knockout of IFT172 or depletion of IFT80 leads to strong ciliary assembly defects (Beales et al , 2007; Tsao & Gorovsky, 2008), and mutations or depletions of IFT80, IFT172, IFT57, IFT54 (elipsa), and IFT38 (qilin) disrupt ciliogenesis and lead to cystic kidneys and curled body axis in zebrafish (Sun et al , 2004; Beales et al , 2007; Omori et al , 2008; Lunt et al , 2009). Most importantly, knockout mice for IFT172 (wimple), IFT57 (Hippi), IFT54 (Traf3IP/MIP‐T3), IFT38 (Cluap1), IFT20, and IFT80 display embryonic lethality highlighting their essential roles in ciliogenesis in mammals (Huangfu et al , 2003; Houde et al , 2006; Jonassen et al , 2008; Berbari et al , 2011; Rix et al , 2011; Pasek et al , 2012). How the peripheral IFT‐B components associate with the core to form a functional IFT‐B complex is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…La question du lien de cette orientation dans le rein reste actuellement controversé. Même si IFT88 est directement impliquée dans ce processus, les résultats diffèrent selon les IFT étudiées [17,18]. Le rôle du cil dans la régula-tion des voies de polarité planaire pourrait passer par le contrôle de la maturation et de la position du centrosome dans l'établissement du fuseau mitotique [47].…”
Section: ( §)unclassified